Information Extraction from Unstructured Documents - Jayanthi, R; Nirmala, D (International Journal of Computer Sciences and Engineering, 2025)
In todays scenario the organization of textual information has become a necessity due to the availability of various digital information. The purpose of Text Mining is to process unstructured (textual) information, extract meaningful numeric indices from the text, and, thus, makes the information contained in the text accessible to the various data mining (statistical and machine learning) algorithm. Information Extraction is the technique of automatically extracting information from unstructured and/or semi-structured machine-readable documents. An Information Extraction system target a specific topic or domain based on the user’s interest and searches for information that has more reliance to the domain. Information Extraction tools make it possible to pull information from text document, database, websites or multiple sources. Information Extraction depends on named entity recognition, a sub-tool used to find targets information to extract. This paper presents the review of various Information Extraction techniques such as Supervised, Unsupervised and Semi-supervised Information Extraction and its application.